OBJECTIVIZATION OF THE EFFECT OF A COMPLEX OF PHYSICAL FACTORS IN PATIENTS WITH CARPAL TUNNEL SYNDROME BY ELECTROMYOGRAM TEST - Evgeniya Vladeva (World Science, 2021)
CTS is the most common compression neuropathy with an incidence of 125-515/100 000. It is a result of compression of the median nerve by the transverse carpal ligament. It is observed in 2 to 5% of the general population, more frequently in women.Electromyography is considered the most accurate diagnostic procedure, although it cannot be fully accepted as a gold standard due to the possibility of false positives (about 15%) and false negatives (about 18%) [1]However, because of its low cost, in comparison to other diagnostic methods, its high diagnostic reliability, and the few contraindications to its application, it remains a method of choice for diagnosis and follow-up of the reinnervation of the median nerve in CTS patients.Aim of study. To investigate the effect of a complex of physical factors on the reverse development of symptoms of moderate carpal tunnel syndrome using electromyography.Materials and methods. 57 patients with mild to moderate degree of carpal tunnel syndrome clinically proven by electroneurographic study were еexamined. 38.60% of the patients were with right hand affected, 9 patients (15.80%) with left hand affected and 26 patients (45.60%) with bilateral involvement (n=26). In the last group, we examined both hands, ie 57 patients and 82 hands were investigated.Based on the analysis of our own studies, we applied the following complex physiotherapeutic program to the patients involved in the study: ultrasound, electrophoresis with Nivalin (Galantamine), and traditional kinesitherapy program.In our study, we examined the sensory and motor fibres of the n. medianus. Changes in distal latency, amplitude, and conduction velocity were observed.Results and discussion. The electroneurographic examination we performed showed a statistically significant change (p <0.001) in the normalization of distal latency, conduction velocity and M amplitude in both the sensory and motor fibres of the affected nerve. These results were reported between the first and fourth months after physiotherapy. There is also a tendency for their retention within the next 4-8 months.Correlation analysis shows that there is a very strong, statistically significant (p <0.001) relationship between the ENG parameters for n. medianus sensory and motor fibres conductivity (distant latency, SNAP and conduction velocity) and the treatment performed, which is established even at the first check-up (1-4 months) after end of the treatment, and the results achieved are maintained over time.The statistically significant changes in the values of ENG parametric fibers of n. medianus, we refer to the complex physiotherapy treatment, aimed at improving the trophic and nerve conduction, accelerating the regenerative processes of the nerve structures, improving the trophic and vascularizing the structures located in the carpal tunnel.Last but not least, the fibrolytic action of ultrasound therapy leading to the spreading of fibrous seals, which is quite common in CTS, is also important. Although different in their mechanism of action, the physiotherapeutic procedures included in our program have a synergistic effect aimed at overcoming the functional deficiency and reversing the symptoms of CTS.Conclusions. Our study on the effectiveness of a complex of physical factors in the conservative treatment of the CTS showed that early diagnosis and timely initiation of physiotherapeutic treatment are a prerequisite for achieving very good results in terms of functional recovery of the affected hand and the reverse development of clinical symptoms in patients with proven mild to moderate CTS.The segmental demyelination of the sensory and motor fibers of n. medianus in the initial stages, as a result of its compression in the area of the carpal canal, is a reversible process. An integrated approach to the treatment of CTS, including early diagnosis, prevention and treatment, is the key for success in mild and moderate forms of the syndrome, and competent and timely medical advice is often crucial.